대구수돗물의 THMs 생성특성 - 배기수(Gi Soo Bae); 백윤경(Yoon Kyung Baek); 류기성(Ki Sung Ryu); 신상희(Sang Hee Shin); 이찬형(Chan Hyung Lee) (Daehan hwan'gyeong gonghag hoeji, 2011)
The occurrence of THMs, the characteristics of THMs formation and removal of THMs were investigated. The treatment train of M plant consists of prechlorination, flocculation, sedimentation, filtration, ozonation, activated carbon and postchlorination. The study of THM formation indicated that about 92% of the THMs were formed in the flocculation/sedimentation/filtration process which affected by prechlorination. The formation of THMs was highly correlated to $KMnO_4$ consumption and water temperature in raw water. The regression model had showed 0.72~0.80 of determination coefficient so it could be used to predict the amount of THMs formation in finished water. Compared to the prechlorination process, the THMs formation was reduced in interchlorination process. With the addition of PAC, fewer THMs were formed in PAC-chlorination process than in chlorination-PAC process. Our results showed that air stripping could be used to remove the existing THMs. 정수처리공정별 THMs 현황과 영향인자와의 상관성 등 생성특성을 분석하고 저감할 수 있는 운영방안을 연구하였다. M정수장의 처리공정은 전염소-응집-침전-여과-오존-활성탄-후염소로 구성되어 있다. 공정별 THMs 농도는 응집침전여과의 기본공정에서 92~93%가 생성되어 전염소처리공정이 주된 영향을 미치는 것으로 조사되었다. THMs 생성과 원수수온, $KMnO_4$소비량의 결정계수는 0.80, 0.72로 높게 나타났으며 정수장에서는 원수수온과 $KMnO_4$소비량으로 생성농도를 예측하는 것이 효율적이라 판단된다. 중염소처리를 한 경우 정수 THMs이 전염소처리의 48% 수준으로 나타나, 염소 주입지점만 변경하는 중염소 처리가 THMs 저감에 유용한 방식으로 판단된다. 전구물질 제거를 위한 분말 활성탄 실험에서는 전염소 앞단에 주입하는 경우에 THMs 생성이 줄었다. 생성된 THMs 제거에는 에어스트리핑 방법이 효과가 있었다.